Respuesta :

Answer:

x = -9

Step-by-step explanation:

2x + 8( x + 3 ) = 3( x - 13 )

Dstribute;

2x + 8 ( x + 3 ) = 3 ( x - 13 )

2x + ((8)(x)) + ((8)(3)) = ((3)(x)) - ((13)(3))

2x + 8x + 24 = 3x - 39

Combine like terms;

2x + 8x + 24 = 3x - 39

10x + 24 = 3x - 39

Inverse operations;

10x + 24 = 3x - 39

-3x            -3x

7x + 24 = -39

     -24     -24

7x = - 63

/7       /7

x = -9

first distribute 8 and 3 through parenthesis. this makes the equation
2x+8x+24=3x-39

collect like terms, such as “2x+8x” this becomes 10x. plug in 10x.

10x+24=3x-39. now move variable and constant. 10x-3x=-39-24
collect like terms again. 10x-3x becomes 7x.

7x=-39-24.
-39-24=-63

7x=-63 divide both sides by 7.

x=-9